Curative Effects of Pomegranate and Ginger on Hepatic and Renal Functions of Indomethacin-Induced Peptic Ulcers in Albino Rats - Shekha, Mudhir S.; Abdulwahid, Muhsin J.; Hamadamin, Peshraw S.; Ismail, Trifa F.; Hamad Bakir, Saman R.; Ibrahim, Laween M.; Ahmed, Lana M. (Science Journal of University of Zakho, 2017)
A peptic ulcer is one of the more severe diseases and most classic treatment protocol produce adverse drug reactions. Therefore, this study aimed to examine the therapeutic effects of two natural extracts, namely Pomegranate and Ginger, on indomethacin-induced gastric ulcer in rats. Animals were divided into five groups; 1. Normal control group, 2. An ulcer control group Indomethacin (0.3 mg /rats), 3. Omeprazole (3 mg /rats), a4. Pomegranate (40 mg /rats), 5. Ginger (20 mg /rats).  The ulcers were induced made from groups 2 - 5 by oral administration of Indomethacin. Rats subjected to indomethacin administration showed significant ulceration in the glandular area of their stomachs compared to normal control rats. In addition, significant elevations S.GPT, S.GOT, S. creatinine and S. Urea (P< 0.05) were observed. Alternatively, pretreatment with pomegranate and ginger significantly corrected macroscopic and biochemical parameters. These results demonstrate that administration of either pomegranate and ginger supplementation have an essential role in the prevention of ulceration induced by NSAIDs. Furthermore improved liver and kidney functions and reduced hepatoto and nephrotoxicities.
Keywords: Peptic ulcer; Ginger; indomethacin; hepatic and renal functions; rats